2018
DOI: 10.1002/bit.26526
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum hemagglutinin‐mediated in situ break‐up of human induced pluripotent stem cell aggregates for high‐density suspension culture

Abstract: Large numbers of human induced pluripotent stem cells (hiPSCs) are required for making stable cell bank. Although suspension culture yields high cell numbers, there remain unresolved challenges for obtaining high-density of hiPSCs because large size aggregates exhibit low growth rates. Here, we established a simple method for hiPSC aggregate break-up using botulinum hemagglutinin (HA), which specifically bound with E-cadherin and disrupted cell-cell connections in hiPSC aggregates. HA showed temporary activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…This method stimulates proliferation through disruption of cell‐cell contact within compacted aggregation and achieves higher hiPSC yields in well‐preserved pluripotency. A recent study reported that temporary disruption of E‐cadherin‐mediated cell–cell adhesion using HA is a simple in situ method for hiPSC aggregate break‐up in bioreactors (Figure ) . HA‐mediated break‐up of hiPSC aggregates showed a higher number of live cells and higher expansion fold compared with aggregates dissociated using enzymatic digestion.…”
Section: Bioprocess Design Considerations To Enhance Scalable Expansimentioning
confidence: 99%
See 2 more Smart Citations
“…This method stimulates proliferation through disruption of cell‐cell contact within compacted aggregation and achieves higher hiPSC yields in well‐preserved pluripotency. A recent study reported that temporary disruption of E‐cadherin‐mediated cell–cell adhesion using HA is a simple in situ method for hiPSC aggregate break‐up in bioreactors (Figure ) . HA‐mediated break‐up of hiPSC aggregates showed a higher number of live cells and higher expansion fold compared with aggregates dissociated using enzymatic digestion.…”
Section: Bioprocess Design Considerations To Enhance Scalable Expansimentioning
confidence: 99%
“…Another recent study demonstrated that spontaneous deviation in hiPSC colony center was suppressed by relaxation of E‐cadherin‐mediated adherens junctions via addition of botulinum hemagglutinin (HA), an E‐cadherin function‐blocking agent. It was found that cell adhesion and cytoskeletal rearrangements occurred in hiPSC colonies by promoting cell migration through HA‐mediated relaxation of cell–cell junctions . The coordinated regulation of balance between cell–cell and cell–substrate interactions through cell migration leads to the prevention of nuclear laminA/C accumulation in hiPSC colony center .…”
Section: Bioprocess Design Considerations To Enhance Scalable Expansimentioning
confidence: 99%
See 1 more Smart Citation
“…Non-enzymatic detachment is also available by changing temperature or pH [18][19][20]. Aggregate culture in bioreactors may not necessarily need a detachment step for harvesting [21][22][23][24][25]. Next steps are washing and volume reduction, which can be done by centrifugation or tangential flow filtration on a large scale by using automated commercial devices (kSep systems and Terumo BCT).…”
Section: Current Manufacturing Strategies For Stem Cell Therapymentioning
confidence: 99%
“…Bioreactor expansion of hPSCs on microcarrier is troublesome for clinical application because it needs an extra step for microcarrier separation from the final cell harvest. On the other hand, aggregate culture in bioreactors may not necessarily need a detachment step for harvesting [21][22][23][24][25] and clinically relevant numbers of cells can be produced in a single bioreactor as aggregate [21,[106][107][108].…”
Section: Integrated System For Large-scale Expansion and Differentiatmentioning
confidence: 99%